Optimal channel selection in parallel scheduling of heterogeneous network based on competitive channel non-cooperative game model. Issue 1 (6th February 2020) - Cheng, Yuan; Zhou, Yucai
In order to improve the parallel scheduling performance and channel balance of heterogeneous network, an optimal channel selection algorithm for parallel scheduling of heterogeneous network based on competitive channel non-cooperative game model is proposed in this paper. In this algorithm, the channel model of heterogeneous network is constructed, and the impulse response frequency doubling technology is adopted to spread the heterogeneous network channels. The simulation results show that this proposed method can improve equalisation and anti-interference ability of channels in optimal channel selection in parallel scheduling of heterogeneous network and it provides the maximum channel transmission bit error rate of 0.35 and channel transmission bit error rate of 0 at signal-to-noise ratio of 50 dB, which indicates that the bit error rate of the receiving end is small. With this method, the end-to-end time delay in parallel scheduling of heterogeneous network is reduced and the channel impulse response time is about 0.4~0.6 seconds, which improves the stability and accuracy of parallel scheduling of heterogeneous network.